#### Answer

$-i$

#### Work Step by Step

Factor out as many $i^4$ as possible.
$i^{-13}=(i^4)^{-3}*i^{-1}$
Know that $i^4=1$. Substitute, and simplify.
$(i^4)^{-3}*i^{-1}=1^{-3}*i^{-1}=\frac{1}{i}=-i$

Published by
Pearson

ISBN 10:
0321671791

ISBN 13:
978-0-32167-179-0

$-i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.